The Use of the Sort Card Method as an Effort to Improve the Ability to Memorize Dhikr Readings After Prayer in Aswaja Lessons at MI Pembangunan Lamongan - Muktinin; Mustaghfirin (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to determine the improvement of Aswaja learning outcomes in dhikr material through the application of the Sort Card method to fourth grade students of MI Pembangunan Lamongan. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were fourth grade students of MI Pembangunan Sidomukti Lamongan. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The learning model used in this study is the Sort Card method. The Sort Card learning method is one of the learning models that can motivate students to be enthusiastic about learning. Because students will be motivated to get the highest score and shout the most cheers. This learning model is very interesting and fun for every student to apply to all subjects. The results of the study show that the application of the Sort Card method can improve learning outcomes in dhikr material for fourth grade students of MI Pembangunan Sidomukti Lamongan. Student activity by applying the Sort Card method increased from 75% in cycle I to 98% at the end of cycle II. Similarly, what happened in the teacher's observation also increased from cycle I by 79% to 100% in cycle II. The results of students' classical cognitive completion in cycle I were 15 students or 84%. However, after the researcher conducted further research in cycle II with various findings in cycle I, students' classical learning completion became very high. Of the 23 students, 21 students completed or 100% and 2 students were absent due to illness. Thus, it can be concluded that the application of the Sort Card learning method can improve students' ability to memorize dhikr material.